Disseminated Histoplasmosis as a Cause of a Small Bowel Mass and Cholestatic Liver Injury in an Immunocompetent Host: A Case Report - Alice Leah Kerkham; Martin David Weltman; Zoe Jennings; Han Liem (Case Reports in Gastroenterology)
Introduction: Disseminated histoplasmosis is a rare cause of granulomatous, cholestatic liver disease. It can also manifest with gastrointestinal (GI) tract involvement, usually with ulceration or mucosal thickening, but is rarely reported as a cause of mass lesions in the GI tract. It is also very rare for disseminated histoplasmosis to present in an immunocompetent host. Case Presentation: We present a case of cholestatic liver disease and a small bowel mass in a 50-year-old male that has not previously been described in an immunocompetent host. Conclusion: Timely diagnosis requires a high index of suspicion, particularly if there has been exposure to high-risk environments such as contaminated soils, as delayed diagnosis is associated with significant mortality.